PENGUKURAN USABILITY PADA APLIKASI SKRIPSI DAN KERJA PRAKTEK (SISKP) MENGGUNAKAN SYSTEM USABILITY SCALE - Sandra Lihawa; Manda Rohandi; Roviana H. Dai (Diffusion: Journal of Systems and Information Technology, 2021)
Information system plays an essential role in higher education institution, particularly the use of Thesis Information System and Job- Training (SISKP) application in Department of Informatics Engineering State University of Gorontalo. One of the most significant components in building a system is having usability that is easy to learn, use, and encourage the users to complete their tasks. Nevertheless, there is no current investigation measuring the SISKP application. Therefore, this research intends to determine the level of usability in the SISKP application based on lecturer's and informatics engineering students' perceptions. The measurement method in this condition uses the System Usability Scale (SUS) because the users can give subjective assessments. The result of this research obtain 72 scores of the SUS for SISKP application which includes in Grade C and classifies as a good category, while the NPS gets a Passive label that is the users who do not recommend SISKP or those who gave negative rating toward SISKP. Hence, for further investigation, it is suggested to explore the factors affecting the lower score of usability on the SISKP application.